Lymphocytic interstitial pneumonia with tiny cysts of peribronchovascular distribution on CT. Issue 12 (6th August 2020) - Hanafiah, Mohammad; Johari, Bushra; Abdul Kadir, Roqiah Fatmawati; Bakar, Nor Salmah; Baharuddin, Hazlyna
Abstract: Cysts are a common finding of lymphocytic interstitial pneumonia (LIP) on imaging. Usually, they are limited in number and size. Tiny and numerous cysts of peribronchovascular distribution are less typical but a recognized appearance in LIP. Abstract : Cysts are a common finding of lymphocytic interstitial pneumonia (LIP) on imaging. Usually, they are limited in number and size. Tiny and numerous cysts of peribronchovascular distribution are less typical but a recognized appearance in LIP.